Information Storage and Management: Storing, Managing, and Protecting Digital Information - Somasundaram, G. (Wiley Publishing, 2011)
The spiraling growth of digital information makes the ISM book a "must have" addition to your IT reference library. This exponential growth has driven information management technology to new levels of sophistication and complexity, exposing a skills gap that challenge IT managers and professionals alike. The ISM book, written by storage professionals from EMC Corporation, takes an ‘open’ approach to teaching information storage and management, focusing on concepts and principles – rather that product specifics – that can be applied in all IT environments